Education and Ideologies of the Knowledge Economy: Europe and the Politics of Emulation - Michael Peters (Social Work & Society, 2004)
The Austrian philosopher Ludwig Wittgenstein famously proposed a style of philosophy that was directed against certain pictures [bild] that tacitly direct our language and forms of life. His aim was to show the fly the way out of the fly bottle and to fight against the bewitchment of our intelligence by means of language: "A picture held us captive. And we could not get outside it, for it lay in our language and language seemed to repeat it to us inexorably" (Wittgenstein 1953, 115). In this context Wittgenstein is talking of philosophical pictures, deep metaphors that have structured our language but he does also use the term picture in other contexts (see Owen 2003, 83). I want to appeal to Wittgenstein in my use of the term ideology to refer to the way in which powerful underlying metaphors in neoclassical economics have a strong rhetorical and constitutive force at the level of public policy. Indeed, I am specifically speaking of the notion of 'the performative' in Wittgenstein and Austin. The notion of the knowledge economy has a prehistory in Hayek (1937; 1945) who founded the economics of knowledge in the 1930s, in Machlup (1962; 1970), who mapped the emerging employment shift to the US service economy in the early 1960s, and to sociologists Bell (1973) and Touraine (1974) who began to tease out the consequences of these changes for social structure in the post-industrial society in the early 1970s. The term has been taken up since by economists, sociologists, futurists and policy experts recently to explain the transition to the so-called 'new economy'. It is not just a matter of noting these discursive strands in the genealogy of the 'knowledge economy' and related or cognate terms. We can also make a number of observations on the basis of this brief analysis. First, there has been a succession of terms like 'postindustrial economy', 'information economy', 'knowledge economy', 'learning economy', each with a set of related concepts emphasising its social, political, management or educational aspects. Often these literatures are not cross-threading and tend to focus on only one aspect of phenomena leading to classic dichotomies such as that between economy and society, knowledge and information. Second, these terms and their family concepts are discursive, historical and ideological products in the sense that they create their own meanings and often lead to constitutive effects at the level of policy. Third, while there is some empirical evidence to support claims concerning these terms, at the level of public policy these claims are empirically underdetermined and contain an integrating, visionary or futures component, which necessarily remains untested and is, perhaps, in principle untestable.